Imposing Cooperation: Institutions and the Efficiency of Cooperative Organizations - Galang, Roberto Martin N (Archīum Ateneo, 2013)
What happens when cooperative organizations are created by government fiat in an emerging market? Cooperatives in developed countries originate from the ability of local communities to solve social problems. The associated skills generated by cooperative formation encourage positive spillovers that enable a virtuous cycle of improved civic capacity and even more cooperative formation. However, in emerging markets, cooperatives may be generated by government decree rather than optimal social forces. As such, these cooperatives may instead suffer from the negative spillovers from the socio-political dysfunctions of their surrounding environment. Through an analysis of the performance of electric cooperatives in the Philippines, we find that not only are cooperatives less efficient than their investor- owned counterparts, their performance is also more sensitive to the quality of the local government that surrounds them. We similarly discover positive efficiency gains for firms that operate in areas with larger communities of cooperatives.